Effectiveness, safety, and endothelial function effects of atorvastatin lipid-lowering therapy in coronary heart disease patients undergoing percutaneous coronary intervention - M. P. Mal’gina; O. I. Ignatyeva; N. V. Moroshkina; Yu. V. Skorobogatova; A. O. Nedoshivin; O. A. Berkovich (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study lipid-lowering and pleiotropic atorvastatin effects on lipid metabolism, endothelial function, fibrinogen level in coronary heart disease (CHD) patients who underwent myocardial revascularization (percutaneous coronary intervention). Material and methods. The study included 40 CHD patients who underwent successful coronary angioplasty and stenting. Inclusion criteria were: primary hyperlipidemia with total cholesterol (CH) level >4,5 mmol/l, low-density CH (LDLCH) level >2,5 mmol/l, and triglycerides level ≤3,5 mmol/l. Initial atorvastatin dose was 20 mg/d. Endothelial function was assessed in reactive hyperemia test, with calculation of endothelium-dependent vasodilatation (EDVD) parameter. Carotid artery ultrasound, with intima-media thickness assessment, was performed.The participants were examined at baseline and after 26 therapy weeks. Results. By the end of 14-week therapy period, target LDL-CH level <2,5 mmol/l was achieved in 56% of the patients, and by the end of Week 26 – in 74%. Mean EDVD was 2,8±1,23 at baseline and 2,984±0,881 26 weeks later (р=0,12). Baseline and control negative EDVD percentage was 56,5% and 34,78%, respectively. Therefore, long-term atorvastatin therapy was associated with improved EDVD, decreased negative EDVD percentage, and improved vasoactive endothelial function. Atorvastatin dose of 20 mg/d caused no clinically significantly adverse events during 26-week therapy course. Conclusion. Lipid-lowering therapy with atorvastatin is highly effective and safe. Due to its pleiotropic action, the medication should be used in patients after myocardial revascularization.